Tinjauan Hukum Tindak Pidana Perampasan Dengan Kekerasan ( Begal) - Anis Curnia (JOURNAL OF SHARIA ECONOMICS, 2022)
The crime of robbery is one form of crime that has become a serious concern in the criminal justice system. The phenomenon of robbery has caused deep concern in society, because this incident often causes significant material losses, psychological trauma, and even takes the lives of victims. This is what makes the author interested in conducting this study with the aim of 1. To analyze the factors that cause robbery crimes. 2. To find out the legal sanctions for perpetrators of theft and robbery with violence (Begal). using the Normative Juridical research method. The results of the research that has been conducted show that robbery and robbery crimes often occur due to weak social control triggered by anomie in society. The main factors that drive the perpetrators are economic inequality and low education, which encourage individuals to take shortcuts. Prevention efforts require increasing access to education and reducing economic disparities. Robbery, as a form of violent theft, is regulated in Article 365 of the Criminal Code with the threat of severe penalties of up to 15 years in prison or the death penalty. Although the rules are clear, weak law enforcement and light sentences trigger high cases. The application of strict sanctions is necessary to create a deterrent effect and maintain public order.